2018
DOI: 10.1016/j.gep.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-induced alterations in the expression of chromatin modifying enzymes and the transcriptional regulation of imprinted genes

Abstract: Embryo culture and assisted reproductive technologies have been associated with a disproportionately high number of epigenetic abnormalities in the resulting offspring. However, the mechanisms by which these techniques influence the epigenome remain poorly defined. In this study, we evaluated the capacity of oxygen concentration to influence the transcriptional control of a selection of key enzymes regulating chromatin structure. In mouse embryonic stem cells, oxygen concentrations modulated the transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Thus, these results could partly explain the increased global methylation level observed in fetuses of the VET group. The TET family of genes is thought to play a role in active genomic demethylation and the resetting of the epigenome (Inoue & Zhang, ; Seiler et al, ; Skiles et al, ). According to our results, TET2 and TET3 were increased in fetuses of the IVC group compared with two other groups, which revealed the reason for the decreased global methylation level of the IVC group.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, these results could partly explain the increased global methylation level observed in fetuses of the VET group. The TET family of genes is thought to play a role in active genomic demethylation and the resetting of the epigenome (Inoue & Zhang, ; Seiler et al, ; Skiles et al, ). According to our results, TET2 and TET3 were increased in fetuses of the IVC group compared with two other groups, which revealed the reason for the decreased global methylation level of the IVC group.…”
Section: Discussionsupporting
confidence: 93%
“…At the later stage of EZH2 downregulation, H3K27me3 is demethylated, which upregulates p16 and SASP-related genes [15][16][17]. Moreover, EZH2 has been shown to be associated with intracellular oxidative stress [18,19]. These results suggest that EZH2 plays potential roles in cell senescence induced by oxidative stress.…”
Section: Introductionmentioning
confidence: 95%
“…Embryo culture at 5% O 2 , mimicking the hypoxic environment within the female reproductive tract, is believed to improve embryo development. 40,[81][82][83] Recently identified links between oxygen levels and transcriptional control of epigenetic regulators support data demonstrating a role of oxygen tension on imprint establishment [84][85][86] (►Table 3). In a study by de Waal et al, our collaborators found significant differences in placental DNA methylation at imprinted loci based on oxygen tension during embryo culture.…”
Section: How Does Oxygen Tension Affect the Epigenome?mentioning
confidence: 74%
“…Epigenetic differences due to oxygen tension have also been documented in mouse embryonic stem cells, where differences in expression of imprinted genes H19, Igf2, Igf2r, and Peg3 were all noted after incubation at atmospheric oxygen compared with 5% O 2 . 84 Whole-genome effects of oxygen tension have also been examined in bovine embryos. Using a 5-methylcytosine antibody, Li et al found that culture of embryos at 20% O 2 resulted in global hypermethylation, though no changes in gene expression were examined.…”
Section: How Does Oxygen Tension Affect the Epigenome?mentioning
confidence: 99%
See 1 more Smart Citation